Growth, maturation and injuries in high-level youth football (soccer): A mini review - Wik, Eirik Halvorsen (Frontiers in Sports and Active Living, 2022)
Understanding the challenges football (soccer) players face during adolescence is fundamental to avoid disruptions in their development due to injury. This mini review will describe basic concepts of somatic growth and biological maturity, examine data from 53 prospective epidemiological studies on high-level youth football players and discuss how age, growth and maturity may affect the injury patterns observed. Based on the existing evidence, at least every third player sustains an injury during a football season. The thigh (median for studies of boys: 25%, median for girls: 21%), ankle (b: 18%, g: 30%), knee (b: 17%, g: 18%) and hip/groin (b: 14%, g: 10%) are the body parts injured most often, while muscle strains (b: 31%, g: 25%), sprains (b: 20%, g: 27%) and contusions (b: 17%, g: 16%) are the most common injury types. Injury trends are, however, not consistent throughout adolescence, and players’ age, maturity status and position relative to peak height velocity (PHV) have shown to influence the number, type and location of injuries sustained. Despite a high volume of observational injury studies published on high-level youth players, girls (7 studies) and settings outside of Europe (included in 23% of studies) are underrepresented and should receive extra attention in the future. Based on the available epidemiological data, tailored injury reduction programmes can be considered in youth football, alongside application of general training principles such as progression, variation and individualisation which may be especially important during vulnerable phases such as the adolescent growth spurt.